Analisis Orientasi Kewirausahaan terhadap Kinerja Organisasi yang Dimoderasi oleh Modal Sosial pada UMKM Souvenir dan Kerajinan di Desa Kedensari Sidoarjo - Gendut Sukarno; Rofaul Khoiril Anwar (Reslaj : Religion Education Social Laa Roiba Journal, 2022)
This study aims to understand the effect of entrepreneurial orientation on organizational performance and the effect of social capital in moderating entrepreneurial orientation on organizational performance. The location of this research and sampling was carried out in Kedensari Village, Sidoarjo. This study uses data on the distribution of questionnaires as a population and data based on the DISKOPUMKM website in Sidoarjo Regency. This research uses SmartPLS. The results of this study indicate that there is a significant influence on entrepreneurial orientation on organizational performance and the effect of social capital in moderating entrepreneurial orientation on organizational performance. Keywords: Entrepreneurship Orientation, Social Capital, and Organizational Performance